Women's subjective perceptions and background factors associated with poor maternal childbirth experience among induced and spontaneous onset of labour: a two-year tertiary hospital cohort study - Katariina Place; Leena Rahkonen; Katti Adler; Heidi Kruit (BMC, 2023)
Abstract Background Women undergoing induction of labour (IOL) more often have poor childbirth experience compared to women with spontaneous onset of labour (SOL). For understanding and optimizing childbirth experience in IOL, we investigated the subjective maternal reasons and perceptions leading to poor childbirth experience in IOL compared to SOL, as well as the background factors and delivery outcomes associated with the poor experience. Methods Two-year retrospective cohort study included 836/19442 deliveries (4.3%) with poor childbirth experience in induced or spontaneous onset at term in Helsinki University Hospital. Poor childbirth experience occurred in 389/5290 (7.4%) cases of IOL and in 447/14152 (3.2%) of SOL. Childbirth experience was measured after delivery using Visual Analog Scale (VAS) score, with poor experience defined as VAS < 5. The primary outcome of the study were the maternal reasons for poor childbirth experience. The parameters were collected in the hospital database and statistical analyses were performed by using Mann-Whitney U-test and t-test. Results The subjective maternal reasons for poor childbirth experience were pain (n = 529, 63.3%), long labour (n = 209, 25.0%), lack of support by care givers (n = 108, 12.9%), and unplanned caesarean section (CS) (n = 104, 12.4%). The methods of labour analgesia were similar among the women who expressed pain as the main reason compared with those who didn't. When comparing the reasons according to the onset of labour, IOL group more often reported unplanned CS (17.2% vs. 8.3%; p < 0.001) and lack of support by the care givers (15.4% vs. 10.7%; p = 0.04), while SOL group more often named pain (68.7% vs. 57.1%; p = 0.001) and rapid labour (6.9% vs. 2.8%; p = 0.007). In multivariable logistic regression model, IOL was associated with lower risk for pain compared to SOL (adjusted OR 0.6, 95%CI 0.5-0.8; p < 0.01). Primiparas more often reported long labour (29.3% vs. 14.3%; p < 0.001) and concern over own or baby's wellbeing (5.7% vs. 2.1%; p = 0.03) compared to multiparas. Women who feared childbirth more often reported lack of support compared to women with no fear (22.6% vs. 10.7%; p < 0.001). Conclusion The main reasons for poor childbirth experience were pain, long labour, unplanned CS and the lack of support by care givers. The childbirth experience is complex and could be optimized by information, support and presence of care givers especially in induced labour.